2018
DOI: 10.1002/jcp.26262
|View full text |Cite
|
Sign up to set email alerts
|

Acrosomal alkalization triggers Ca2+ release and acrosome reaction in mammalian spermatozoa

Abstract: The sperm acrosome reaction (AR), an essential event for mammalian fertilization, involves Ca permeability changes leading to exocytosis of the acrosomal vesicle. The acrosome, an intracellular Ca store whose luminal pH is acidic, contains hydrolytic enzymes. It is known that acrosomal pH (pH ) increases during capacitation and this correlates with spontaneous AR. Some AR inducers increase intracellular Ca concentration ([Ca ] ) through Ca release from internal stores, mainly the acrosome. Catsper, a sperm spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 80 publications
8
41
0
3
Order By: Relevance
“…The role of Ca 2+ in the regulation of the AR in sea urchin sperm was first suggested by Dan [98], and further evidence was provided by use of the Ca 2+ ionophore A23187 or by simply increasing the external pH in the presence of Ca 2+ . Both treatments initiated the internal polymerization of actin in the acrosomal process [99][100][101][102]. The sperm of starfish has been a particularly useful model to study the egg-jelly signaling molecules for triggering AR as well as for the role played by actin filaments in sperm-egg interaction and penetration (see below).…”
Section: Contribution Of Actin Dynamics To Sperm and Egg Activationmentioning
confidence: 99%
“…The role of Ca 2+ in the regulation of the AR in sea urchin sperm was first suggested by Dan [98], and further evidence was provided by use of the Ca 2+ ionophore A23187 or by simply increasing the external pH in the presence of Ca 2+ . Both treatments initiated the internal polymerization of actin in the acrosomal process [99][100][101][102]. The sperm of starfish has been a particularly useful model to study the egg-jelly signaling molecules for triggering AR as well as for the role played by actin filaments in sperm-egg interaction and penetration (see below).…”
Section: Contribution Of Actin Dynamics To Sperm and Egg Activationmentioning
confidence: 99%
“…To understand how sperm pH i is regulated, it is indispensable to determine where and when it changes in individual cells. Although sperm pH i measurements in suspension have been performed using fluorescence indicators for more than three decades (Schackmann and Boon Chock, 1986;Darszon et al, 2004;Hamzeh et al, 2019), there are few reports of imaging single sperm pH i (Zeng et al, 1996;Chávez et al, 2014Chávez et al, , 2018González-Cota et al, 2015). All these experiments were performed with BCECF (Rink et al, 1982), the most popular fluorescent pH i indicator in cell physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Percoll-separated sperm was washed twice using NCM and stained with 5 μM of the cytoplasmic pH-sensitive dye BCECF-AM [10, 11] or with 5 μM of the cell organelle pH-sensitive marker Lysosensor green DND-189 [28] in NCM, by incubation at 38.5 °C for 30 min. The extracellular dye was then removed by washing the sperm twice in NCM (400 g, 5 min).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, weak bases are able to partition into acidic cell organelles, alkalinizing them and releasing Ca 2+ from them [26, 27]. Recently, Chávez et al [28] reported a similar action of weak bases resulting in the acrosome reaction in mouse and human sperm. In contrast, Loux et al [11] suggested that the relationship between hyperactivated motility and Ca 2+ influx is likely to be weak in stallion sperm cells because analysis of the equine CatSper1 protein revealed species-specific differences in the structure of the pH sensor region.…”
Section: Introductionmentioning
confidence: 99%